Practical consequences – ethical values as the basis for a system of public health management - Sytnik-Czetwertyński, Janusz (Journal of Education, Health and Sport, 2016)
Sytnik-Czetwertyński Janusz. Practical consequences – ethical values as the basis for a system of public health management. Journal of Education, Health and Sport. 2016;6(10):321-330. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.162561 http://ojs.ukw.edu.pl/index.php/johs/article/view/3948 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 02.10.2016. Accepted: 20.10.2016. Practical consequences – ethical values as the basis for a system of public health management Janusz Sytnik-Czetwertyński UKW w Bydgoszczy, Poland Abstract The place of the first and last meeting between the citizen and the system is the hospital. The organisation of its management is basically a condition of human life, later of health and finally, of a dignified death. We could say that the system of managing public health is a basis for the dignity of the nation, a basis for humanity. The hospital is a place of mutual learning between system and citizen, of studying its possibilities. The relationship between individual and public health is virtually unbreakable. We could claim that for the newborn infant, the hospital is the place where statehood first manifests itself. It is a preliminary element, the riser on the steps to the system, an introduction to life . But later, this same system observes the young citizen in his development. The system requires healthy individuals, identifying with it and its division into specific roles. It therefore educates, then indicates the places within its organism which need filling, so that its main functions are maintained. In order to minimise the risks of any potential error, the system defines the possibilities of the citizen. To this end, the means of evaluation in the hospital, later clinic and school, are those most employed. Key words: public health, ethical dilemme, mind-body problem